POTENSI KESESUAIAN LAHAN UNTUK BUDIDAYA KEMIRI SUNAN (Reutealis trisperma) DI KABUPATEN PESAWARAN PROVINSI LAMPUNG MENGGUNAKAN SISTEM INFORMASI GEOGRAFI (SIG) - Lukas Rudy Hadi Saputra; Melya Riniarti; Arief Darmawan (Jurnal Hutan Tropis, 2019)
The fraquenly used of non-renewable fuel causes the oil depletion in nature. Alternative fuels are needed to overcome excessive use and sustainability of oil. Reutealis trisperma could be processed as biodiesel oil, it could replace non-renewable oil. The purpose of this study is to analyze the suitability of land for Reutealis trisperma cultivation and analyze the land recommandation for planting Reutealis trisperma in Pesawaran District, Lampung Province. Determination of sampling points was done by purposive sampling. The analysis was carried out with data on each criteria parameter carried out by processing Arc GIS 10.3 software to obtain altitude maps, rainfall maps, numbers of dry months maps, temperature maps, air humidity maps, slope maps, pH maps, drainage and soil textures. Than, the whole map was being overlay. The results of analysis for suitability land in Pesawaran District found that there were no suitability class S1 (very suitable), S2 (suitable) covering area of 283.70 km2, and S3 (not suitable) covering area of 891.07 km2. Based on the suitability map that has been integrated with the regional spatial design Pesawaran District map, the directions for the cultivation of Reutealis trisperma located in the District of Padang Cermin, with the area of 131.82 km2, Way Lima 24.88 km2 and Marga Punduh 24.39 km2.